Impact of macroeconomic factors on Foreign Direct Investment (FDI) evidence from United States - Ang, Wen Shing; Chin, Jeslyn Jing Wen; Liap, Weng Kee; Lim, Hong Zer; Loh, Chee Yung (2020)
Foreign Direct Investment (FDI) plays a crucial role in speeding up the development and economic growth of a country. In particular, developing countries rely heavily on FDI to promote their economy as they face capital shortage for their development process. FDI not only brings in capitals and technology, but also skills into developing countries. And these ended up helping the countries to grow faster by satisfying the country’s needs. The strong growth performances experienced by United States economy greatly depends on the FDI. FDI generates economic growth by increasing capital formation through the expansion of production capacity, promotion of export growth and creation of employment in United States. FDI inflows of United States started fluctuating from 2005Q1 to 2019Q1 and this high volatility of United States FDI inflows drew the researchers’ attention to examine the factors affecting FDI inflows in Malaysia by using the annual data from year 1993Q2 until 2019Q1. Multiple linear regressions model is applied to study the relationship between explanatory variables (export, exchange rate and taxation) and explained variable (United States FDI inflow). Empirical results show that export, exchange rate and taxation significantly and positively affect United States FDI inflows.